2012
DOI: 10.1007/s10461-012-0136-y
|View full text |Cite
|
Sign up to set email alerts
|

Injection Drug Use and HIV Antiretroviral Therapy Discontinuation in A Canadian Setting

Abstract: We investigated whether drug-related behaviors predicted antiretroviral therapy (ART) discontinuation among a cohort of injection drug users (IDU) in a Canadian setting. Cox regression analyses were used to investigate the impact of drug use patterns on rates of ART discontinuation among a sample of HIV-positive IDU in Vancouver, Canada between May 1996 and April 2008. In total, 408 HIV-positive IDU initiated ART during the study period, among whom 257 (63.0%) discontinued ART at least once. Rates of ART disco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…A study conducted among PWID with current and histories of injection drug use in Denmark found ART adherence of less than 90% in 55% of PWID (defined by satisfying the 90% medication adherence and remaining in treatment to the end of the study evaluation) (31). A long term follow-up study among PWID with current and histories of injection drug use in Canada from 1996 through 2008 recruited over 400 HIV positive PWID, and only 63% remained adherent over the entire adherence analysis period (defined by satisfying the 90% medication adherence and remaining in treatment to the end of the study evaluation) (32). Among 350 PWID with current and histories of injection drug use that were analyzed as part of the ALIVE study in Baltimore (33), adherence was measured over a five year period of HIV treatment, and the results showed that only 26.7% of participants were compliant with ART therapy (defined by 90% of medication taken during follow-up periods) (34).…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted among PWID with current and histories of injection drug use in Denmark found ART adherence of less than 90% in 55% of PWID (defined by satisfying the 90% medication adherence and remaining in treatment to the end of the study evaluation) (31). A long term follow-up study among PWID with current and histories of injection drug use in Canada from 1996 through 2008 recruited over 400 HIV positive PWID, and only 63% remained adherent over the entire adherence analysis period (defined by satisfying the 90% medication adherence and remaining in treatment to the end of the study evaluation) (32). Among 350 PWID with current and histories of injection drug use that were analyzed as part of the ALIVE study in Baltimore (33), adherence was measured over a five year period of HIV treatment, and the results showed that only 26.7% of participants were compliant with ART therapy (defined by 90% of medication taken during follow-up periods) (34).…”
Section: Discussionmentioning
confidence: 99%
“…No one refused to participate or dropped out of the study and participants were provided an honorarium ($30 CAD). Interviews were facilitated using an interview guide adapted from our previous qualitative studies with PLHIV who use drugs [4143] and revised to focus on influences on ART adherence identified through analyses of ACCESS data [34, 44, 45]. Interviews were 20–70 min in length, audio recorded, and transcribed.…”
Section: Methodsmentioning
confidence: 99%
“…57 While research from North America has shown that optimal outcomes from ART can be achieved in prisons, 245 a large body of work from a range of settings shows that among PWID, incarceration is often strongly associated with poor access and adherence to ART, premature discontinuation of ART, and low rates of viral suppression. 246249 It appears that problems ensuring access to ART and related care within North America occurs throughout the incarceration process (e.g., in detention, during transfers, at discharge), and low access and adherence is shaped by high rates of HIV-related stigma and concerns about breaches of privacy within prison systems. 246,250 (see web appendix VII).…”
Section: Drug-related Incarceration and Healthmentioning
confidence: 99%